Distance Control System to Increase Precision And Stability of Glass Cleaning Robot - Bambang Sampurno; Arief Abdurrakhman; Herry Sufyan Hadi; Heri Joestiono; Amanda Fitri Saudzah (Institut Teknologi Sepuluh Nopember, 2019)
Glass is a widely used material today. One of them is as a window of a building. As the material is easily broken, glass is very vulnerable in the cleaning process. This causes the process of cleaning the glass cannot be done carelessly. To overcome these problems, one of them is to replace the work done by humans with machines or robots. The glass cleaning robot was created as a glass cleaner replacing the conventional workforce. One of the most important elements in the operation of glass cleaner robots is the robot glass distance control system against glass edges using proximity sensors. At a distance of 35 cm, the proximity sensor will send a signal back to the microcontroller and forwarded to the input dc motor so that the value changes rpm on the motor with pwm value of 205 each for the left motor and 150 for the right motor for 1 second so that The robot will turn clockwise. From the tested, gotten the response of distance control system based on the PWM value vs time. It shows that the system has a good response to listing programs that have been created. It does not have a research value different from the setting point and fast to achieve stable conditions. In the design of cleaning fluid monitoring system on glass cleaning robot used water level sensor. It used Bluetooth as a wireless system to display height of water in container cleaning fluid.